2019
DOI: 10.7759/cureus.5861
|View full text |Cite
|
Sign up to set email alerts
|

Value of Elastography in Differentiating Benign from Malignant Breast Lesions Keeping Histopathology as Gold Standard

Abstract: Background: Breast cancer is the most common cancer in females, both in developed and developing countries. Pakistan has the highest breast cancer incidence rate in Asia. Guidelines recommend screening for detecting breast cancer with mammography and ultrasonography (US). Shear-wave elastography (SWE) is a newer technique that can aid additional characterization of breast lesions. Objective: The aim of this study was to determine the diagnostic accuracy of breast ultrasound elastography in differentiating beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Similarly, Farooq et al, (9) found that the overall average mean elastography value was 108.45 kPa ± 52.75. The mean elastography (E Mean) value for benign breast lesions was 48.96 kPa ± 42.32 and 132.78 kPa ± 42.32 for malignant lesions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, Farooq et al, (9) found that the overall average mean elastography value was 108.45 kPa ± 52.75. The mean elastography (E Mean) value for benign breast lesions was 48.96 kPa ± 42.32 and 132.78 kPa ± 42.32 for malignant lesions.…”
Section: Discussionmentioning
confidence: 76%
“…However, Farooq et al, (9) reported that their study sample comprised of 155 women with a mean age of 45.41 ± 14.24 years (range 20-70 years).…”
Section: Discussionmentioning
confidence: 96%
“…American College of Radiology Breast Imaging Reporting and Data System(ACR-BIRADS) is used for the evaluation and follow-up recommendations of breast lesions detected by US. However, radiologists’ subjective classification differences may affect diagnostic performance, thereby leading to overtreatment, especially for lesions with BI-RADS 4 category ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 3 ] In breast imaging, several studies have indicated that elastography can help evaluate malignant risk. [ 4 , 5 ] In addition, assessment of breast mass by stiffness has significant diagnostic value. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In breast imaging, several studies have indicated that elastography can help evaluate malignant risk. [4,5] In addition, assessment of breast mass by stiffness has significant diagnostic value. [6] Elastography can be classified into 2 systems according to the methods of applying strain: strain elastography and shear wave elastography (SWE).…”
Section: Introductionmentioning
confidence: 99%